T Cells Plead for Rejuvenation and Amplification; With the Brain’s Neurotransmitters and Neuropeptides We Can Make It Happen - Levite, Mia (Frontiers in Immunology, 2021)
T cells are essential for eradicating microorganisms and cancer and for tissue repair, have a pro-cognitive role in brain, and limit CNS inflammation and damage upon injury and infection. However, in aging, chronic infections, acute SARS-CoV-2 infection, cancer, chronic stress, depression and major injury/trauma, T cells are often scarce, exhausted, senescent, impaired/biased and dysfunctional. People with impaired/dysfunctional T cells are at high risk of infections, cancer, other diseases and mortality, and become multi-level burden on other people, organizations and societies. It is suggested that ‘Nerve-Driven Immunity’ and ‘Personalized Adoptive Neuro-Immunotherapy’ may overcome this problem. Natural Neurotransmitters and Neuropeptides: Glutamate, Dopamine, GnRH-II, CGRP, Neuropeptide Y, Somatostatin and others, bind their well-characterized receptors in naïve/resting T cells, and induce multiple direct, beneficial and therapeutically-relevant effects. They can induce/increase: gene expression, cytokine secretion, integrin-mediated adhesion, chemotactic migration, extravasation, proliferation and killing of cancer. We recently found that some Neurotransmitters/Neuropeptides also decrease significantly PD-1. By inducing these beneficial effects in naïve/resting T cells at different times after binding their receptors (i.e. NOT by single effect/mechanism/pathway) Neurotransmitters/Neuropeptides by themselves can activate, rejuvenate and improve T cells. ‘Personalized Adaptive Neuro-Immunotherapy’ is a novel method for rejuvenating and improving T cells safely and potently by Neurotransmitters/Neuropeptides, consisting of personalized diagnostic and therapeutic protocols. Patient’s scarce and/or dysfunctional T cells are activated ex vivo once by pre-selected Neurotransmitters/Neuropeptides, tested and re-inoculated to patient’s body. The Neuro-Immunotherapy can be actionable and repeated whenever needed, and allows other treatments. The Neuro-Immunotherapy calls for testing safety and efficacy in clinical trials.